JENIS DAN BENTUK AFIKSASI DALAM BAHASA TIDORE (TINJAUAN MORFOLOGI) - Halil, Muamar Abd.; Hilmi, Hubbi Saufan (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
This research aims to describe the types and forms of affixation in the Tidore language used by speakers in the village of Maitara. This research was a qualitative descriptive research. The sample or informants in this study were the speakers of the Tidore language in the village of Maitara, the city of Tidore Islands, which had been selected using a purposive sampling technique. The data collection method is in the form of listening and speaking. The data in this study were analyzed using the expansion technique and the mark reading technique. The types of affixation in Tidore include prefixes and suffixes. The prefix form in Tidore language in Maitara village is in the form of ma-, la-, se-, sa-, and to-, while the suffix form in Tidore language used by speakers in Maitara village, Tidore Islands city only has one form, namely -i .